A Brief Analysis of Spiritual Care in Christian Healthcare Services: The Case of Missionaries' Historical Efforts in Establishing Leprosy Treatment in China - LIU Shibo, (Journal of Research for Christianity in China (JRCC), 2025)
This paper examines the history of Western missionaries establishing leprosy medical and social relief services in China during the nineteenth and twentieth centuries. Employing perspectives and theoretical approaches from cultural anthropology and historical anthropology, it investigates the ethical implications of Christian spiritual care (also known as “spiritual care”) in social healthcare services, analyzes the intrinsic motivations driving missionaries to provide social services in China, and explores how their " examines the role and societal impact of Christian spiritual care ethics within social healthcare services. It analyzes the intrinsic motivations driving missionaries' social service initiatives in China and the process by which their “spiritual capital” was transformed into social resources, along with its practical outcomes. This exploration seeks to uncover the historical significance and contemporary implications of missionaries' contributions to modern public health in China for the development of contemporary social services.
Keywords: Christianity, spiritual care, leprosy treatment